Implementation of Blue Ocean Strategy: Review of Previous Cases - Hokianto, Hugo Fostin (Yayasan Sinergi Kawula Muda, 2023)
Blue Ocean Strategy is considered to be an unique strategy to be used by business owners, as its was first introduced as a way to “create profit by finding new market and less focusing on competing”. However, as much as the strategy have been introduced and used, how does it perform in practice? What is Blue Ocean Strategy main points, and what are the theoretical research thinks about the strategy? These has yet to be unanswered, hence using qualitative research with literature review method to conduct research, the discussion points out what makes blue ocean distinctive as a strategy, the theoretical perspectives from many authors about blue ocean strategy, and the example cases in implementing Blue Ocean Strategy.